Improving Volleyball Underhand Serve Learning Outcomes Through the Wheelbarrow Game Approach - Haslindah, Haslindah; Bismar, Ahmad Rum; Suwardi, Suwardi; Hudain, Muh. Adnan; Ramli, Ramli (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of the study was to determine the improvement of learning outcomes of mini volleyball underhand passing through the Pushcart Game Approach for Students of UPT SPF SD Inpres Bertingkat Bara-Barayya II. This study is a classroom action research using several cycles (pre-cycle, cycle I and cycle II) to see the improvement of students after being given the crab walk game. The study was conducted 2 times in one meeting so the total meetings for 2 cycles were 4 times besides one meeting for the pre-cycle. The number of samples was 24 grade V students. The indicator of learning completeness is if students get a score above 80. The results of the study showed that in the pre-cycle activities, the number of students who completed learning was 4 students and did not complete as many as 20 students or 17% of students completed and 83% of students did not complete. In cycle I, the number of students who completed learning was 6 students and 18 students did not complete or 25% of students completed and 75% of students did not complete, while in cycle II there was a significant increase in student learning completeness to 24 students completed or 100%. The conclusion is that the wheelbarrow game can improve the learning outcomes of mini volleyball underarm serve in UPT SPF students at SD Inpres Bertingkat Bara-Barayya II.